A BRIEF HISTORY OF THE ORIGIN OF THE WORLD MEDICAL SCIENCE AND HIGH-TECH MEDICAL CARE (REVIEW) - A. S. Kiselev (Сеченовский вестник, 2022)
The article views the history of formation of the first medical schools of ancient world and further development of medical science in the modern world. Particular attention is paid to the development of scientific component of practical medicine.